Comparison of coping strategies and supports between aboriginal and non-aboriginal people living with HIV in Ontario. Issue 1 (2nd January 2016) - Jaworsky, Denise; Benoit, Anita; Raboud, Janet; O'Brien-Teengs, Doe; Blitz, Sandra; Rourke, Sean B; Burchell, Ann N; Loutfy, Mona R; ,
Abstract : Complex historical and cultural factors have contributed to the HIV epidemic among Aboriginal populations in Canada. This study assesses social supports, adaptive and maladaptive coping mechanisms, stress, and mastery of Canadian-born Aboriginal and Canadian-born Caucasian people living with HIV in Ontario and posits that coping and social support are important micro- and meso-level factors associated with the epidemic. This cross-sectional analysis included questionnaire data collected from 2007 to 2011 at HIV clinics in Toronto. Categorical and continuous variables were compared using chi-square and Wilcoxon rank sum tests, respectively. Correlates of social support and coping were determined using univariate and multivariable linear regression. The analysis included 70 Aboriginal and 665 Caucasian participants. Aboriginal participants had lower levels of employment, education, and annual household income. Aboriginal participants reported more overall (7 vs. 4, p  = 0.0003), ongoing (4 vs. 2, p  = 0.0004), and early childhood (2 vs. 1, p  = 0.02) stressors. Maladaptive coping, adaptive coping, and mastery scores were similar between Aboriginal and Caucasian participants. In multivariable analysis, injection drug use and lower education levels were significant correlates of higher maladaptive coping and lower overall support scores. Despite numerous socioeconomic challenges and personal stressors, Aboriginal people living with HIV who are accessing care exhibited comparable coping and mastery scores to Canadian-born Caucasian people living with HIV, suggesting remarkable strengths within Aboriginal people living with HIV and their communities.